Genetic relatedness of Trichoderma isolates antagonistic against Fusarium oxysporum f.sp. dianthi inflicting carnation wilt - Shanmugam, V; Sharma, Vivek; Ananthapadmanaban (Folia microbiologica, 2008)
Twenty-eight isolates of Trichoderma belonging to four different species were screened in vitro for their antagonistic ability against Fusarium oxysporum f.sp. dianthi causing carnation wilt. Three different levels of antagonism observed in dual plate assay were further confirmed by cell-free culture filtrate experiments. Isolates showing class I level of antagonism produced maximum lytic enzymes, chitinases and beta-1,3-glucanases. Genetic variability of 25 selected isolates was assessed by random amplified polymorphic DNA technique and the amplified products were correlated for their level of antagonism. Unweighed pair-group method with arithmetical averages cluster analysis revealed prominent inter-and intraspecific genetic variation among the isolates. Based on their genetic relationship, the isolates were mainly distributed into 3 major groups representing T. atroviride, T. pseudokoningii and T. harzianum, with 20-35% interspecific dissimilarity. However, the polymorphism shown by the isolates did not correlate to their level of antagonism.
Keywords: nemoci rostlin; genetická variace; Phylogeny; antibióza; polymorfismus délky restrikčních fragmentů; půdní mikrobiologie; Fungal Proteins; Plant Diseases; Trichoderma; Genetic Variation; Soil Microbiology; Fusarium; fungální proteiny; Chitinases; chitinasy; fylogeneze; Polymorphism, Restriction Fragment Length; Antibiosis